Diagnosis urine disease based on KNN algorithm and ANN - Azeez, Maytham Salman; Maki, Zinah Muneer (International Journal of Engineering and Technology, 2018)
The Artificial Neural Networks (ANN) are commonly applied in several medical fields for undertaking diagnosis of diseases. ANN can be used for diagnosing the urine bladder as well as nephritis inflammation. This research paper mainly focuses on undertaking the diagnosis of urine disease on the basis of K-Nearest Neighbor Algorithm (KNN) and Artificial Neural Network (ANN). The Acute Inflammation Data Set was employed in the research methodology. The data was collected from the UCI Machine Learning Respiratory which would enhance the successful carrying out of the diagnosis. The collected data is distinguished into inputs as well as targets. The systems will represent the inputs to a neural network. The neural network targets will be recognized as 1’s for infected and as 0’s for non-infected. It is evident from the results that the artificial neural network could be significant for recognizing the infected person. The results which can be obtained from the application of ANN methodology on the basis of the selected signs and symptoms clearly indicates the network ability to comprehend the specific patterns which correspond to the person’s Symptoms-Nearest Neighbor algorithm normally unveils the satisfactory rate at which the diagnosis is done to ascertain the distinction between the infected as well as non-infected urinary system.